The stability of narrow money demand in Germany and aggregate money demand in the EMS: Impact of German reunification - Martin Falk; Norbert Funke (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
This paper shows that the German monetary union not only had an impact on the stability of the narrow money demand in Germany but also on the stability of the aggregate demand for money in two larger European currency areas, consisting of 3 and 7 EMS-countries. However, despite fears harbored earlier the impact was only of a temporary nature and the reunification shock did not trigger permanent disruptions. The empirical results support the continued existence of a remaining close link between real money, output, and the interest rate. This is particularly true for the aggregate demand for money in Europe. In a European Monetary Union, narrow money thus remains a potential candidate as an indicator and/or intermediate target for the European Central Bank.
Keywords: 330